Thymol improves the growth performance of blue foxes by regulating the gut microbiota - Yuan, Chongshan; Chen, Siqi; Sun, Rui; Ren, Lili; Zhao, Tiancheng; Wu, Min; Zhang, Aiwu (Frontiers in Microbiology, 2024)
Introduction: The drawbacks of using antibiotics as feed additives for blue foxes have gradually become apparent; moreover, thymol has wide-spectrum antimicrobial activity and has the potential to replace antibiotics in various animals. However, there are few reports on the effects of thymol on blue foxes. Methods: This study aimed to investigate the effects of different concentrations of thymol on the growth performance, apparent nutrient digestibility, serum biochemical indicators, intestinal morphology, and gut microbiota of blue foxes. Twenty-four male blue foxes (120 ± 5 d) of similar weight (6.05 ± 0.16 kg) were randomly divided into 4 groups. 0, 100, 200, and 300 mg/kg thymol were added to the basal diets of groups C, L, M, and H, respectively. Results: Compared with those in the C group, the addition of 100 mg/kg thymol to the diet significantly increased organic matter (OM) digestibility, crude protein (CP) digestibility, immunoglobulin (Ig) A, IgM, the VH of the duodenum, the CD of the jejunum, the VH of the ileum, and the VH/CD of the ileum (P < 0.05) and strongly significantly increased IgG (P < 0.01). The addition of 200 mg/kg thymol to the diet increased the VH/CD of the duodenum (P < 0.05). The addition of 300 mg/kg thymol to the diet significantly increased the VH and CD of the jejunum (P < 0.05). The addition of 200 mg/kg and 300 mg/kg thymol to the diets increased the final weight (FW) (P < 0.05). Adding 100 mg/kg thymol significantly increased the levels of interleukin-4 (IL-4) and catalase (CAT) compared with those in the other groups (P < 0.05). 16S rRNA gene detection revealed that thymol can change the abundances of Bifidobacterium, Fusobacterium, Allobaculum, Streptococcus, Megasphaera, and Lactobacillus in the gut. Conclusion: The addition of thymol to diets can increase the abundance of Bifidobacterium, Fusobacterium, and Allobaculum, which may contribute to improving the growth performance of blue foxes.